Mercury cycling and isotopic fractionation in global forests. Issue 21 (2nd November 2022) - Wang, Xun; Yuan, Wei; Lin, Che-Jen; Feng, Xinbin
Abstract: Forest ecosystem accounts for 31% of global land areas and plays a key role in the global biogeochemical cycling of mercury (Hg). In this critical review, datasets of Hg flux measurements and Hg isotopic compositions in the environmental compartments of forests in the last three decades are synthesized to examine the budgets of Hg mass balance and storages. The primary goal of this synthesis is to provide insight into the source, transportation, translocation and fate of legacy Hg in forests. Existing data indicate that forests represent the largest atmospheric Hg sink in the terrestrial ecosystem, with atmospheric total Hg deposition of 2200–3400 Mg yr −1 (i.e., relative to 40–65% atmospheric Hg pool size) and 500–1100 Gg of Hg stored in surface soils and vegetation. The climate and land cover changes, deforestation and wildfire re-volatilize several hundred tons of Hg into the atmosphere, thus increasing the ecological risk to the regional and global environments. Vegetative uptake of Hg 0 vapor from air predominantly controls Hg accumulation and isotopic fractionation in the atmosphere and in global forests. With the ongoing Hg emission reduction from anthropogenic sources required by the Minamata Convention, an integrated assessment on the changing biogeochemical processes and isotopic fractionation in response to human and natural perturbations of emissions, climate, and land use is needed. Graphical abstract: UF0001